Exploring the meanings that stakeholders of the Brandfort community ascribe to their experiences of a Dalcroze-inspired workshop. Issue 2 (1st August 2019) - van der Merwe, Liesl; Tempelhoff, Johann Wilhelm Nicolaas; Joubert, Debra
For some time now, urban settlements in the rural areas of South Africa have experienced considerable problems relating to municipal water and sanitation service delivery. In September 2013, as part of a larger investigation in the town of Brandfort in the Free State Province, a transdisciplinary research team, Cultural Dynamics of Water (CuDyWat), conducted a workshop using Dalcroze-inspired activities based on music and movement to generate insight into local water-related problems. The objective was to come to an understanding of the lived experiences of a random group of community members and to contemplate potential solutions to the conundrum. This article reports on a novel application of Dalcroze, with non-musician participants, for the betterment of a social group in crisis. It is argued that Dalcroze-inspired activities are useful to encourage people to express themselves and gain better insight into the problems they face. This approach also serves to strengthen relationships in highly diverse groups.